WATER USERS ASSOCIATIONS AND INDIGENOUS INSTITUTIONS IN THE MANAGEMENT OF COMMUNITY-BASED IRRIGATION SCHEMES IN NORTHEASTERN GHANA - Derbile, Emmanuel Kanchebe (European Scientific Journal, ESJ, 2012)
In northeastern Ghana as in many parts of the Developing World, external development agencies support the formation of Water Users Associations (WUAs) for the management of community-based irrigation schemes. Although WUAs are presumed to be the panacea to the myriad of management problems that bedevil irrigation schemes, this paper argues that they strongly draw on the supportive roles of indigenous institutions for discharging their management responsibilities more effectively. First, WUAs gain legitimacy, power and general acceptability to operate because they have the consent and support of Traditional Authorities (TAs). Secondly, WUAs resort to these traditional authorities for support in setting and enforcing rules relevant for the management and sustainability of irrigation schemes. Thirdly, WUAs manage conflicts but they resort to traditional authorities for resolving difficult conflicts arising from the management of the irrigation schemes. This paper therefore, asserts that the management of community-based irrigation schemes in northeastern Ghana mirrors an Endogenous Development (ED) approach to irrigation management. In this approach, WUAs and TAs complement each other in the roles they play and draw on local resources, power and authority for the management of community-based irrigation schemes.